Online and on land: an examination of Irish arts festivals’ response to Covid-19 - Teevan, David (Irish Journal of Arts Management and Cultural Policy, 2021)
This paper considers the short- to medium-term implication for festival organisations and arts policy writers of changes in festival practice introduced to enable organisations operate and accommodate social distancing regulations introduced to mitigate the spread of Covid-19. At this juncture, it is still too soon to determine the longer-term implications for the Irish arts festival ecology of the public health restrictions introduced to mitigate the spread of Covid-19 during 2020 and 2021. However, research and analysis of the sector over this time has revealed that operational changes, introduced to enable festivals to function while social distancing measures were in place, are becoming imbedded into organisations’ operating systems and post-pandemic strategic planning. In particular, this study indicates that festival organisations envisage maintaining a significantly increased level of dependence on digital technologies in both the creation and delivery of festival programmes. There is also evidence of a growing commitment to sustaining a commitment to longer-form creative collaborations outside the public facing festival period. The paper concludes by exploring some implications these sectoral transformations present Irish arts policy, and argues for the need for ongoing research. In particular, it highlights the importance of developing a greater understanding of the public’s engagement with online festival programming.